Ethnic traditions and general civil universals as components of everyday social practices - Yuliya Sergeevna Panfilova, Anna Aleksandrovna Bespalova,; Chikarova, Galina Igorevna (Opción, 2019)
The aim of the study is to investigate ethnic traditions and general civil universals as components of everyday social practices of the population of the South of Russia via sociological research method. As a result, the use of the national language in the education system is more significant for the townspeople of the region under consideration. The authors came to the conclusion that today the ethnocultural axiological component is represented in everyday social practices to a lesser extent than the general civil one.